Substitution of nitrite with ascorbate in conventional quick cured bacon - Azarcon, Sonia B.; De Leon, Sonia Y. (1977., 1977)
The effect of substitution of 2:1 ascorbate-nitrite ratio on the residual nitrite levels in conventional quick cured bacon was determined. Results showed that residual nitrite levels decreased upon one week's storage for both control and nitrite-substituted bacon. The 2:1 ascorbate-nitrite ratio gave the desired 10-20 ppm residual nitrite level which has been claimed by Mirvish et.al. (1972) in a model system to block nitrosation almost completely. This proves significant in eliminating or reducing the potential hazards of potent carcinogenicity of dimethylnitrosamine in man. Physico-chemical tests such as pH, moisture content, water holding capacity, percentage shrinkage and color determination were also taken. Negative results were obtained from the microbiological examination for the possible risk of Cl. botulinum outgrowth. Sensory evaluation results disclosed that the 2:1 ascorbate-nitrite ratio in conventional quick cured bacon was superior to the control in terms of color, flavor and general acceptability.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Meat -- Preservation